2023
DOI: 10.1029/2022gl100745
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting SMILEs and the CMIP5 Archive to Understand Arctic Climate Change Seasonality and Uncertainty

Abstract: Arctic amplification (AA) is a phenomenon of anthropogenic climate change in which the near-surface air temperatures (SATs) in the Arctic increase more rapidly than do those in the rest of the globe (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 58 publications
1
3
0
Order By: Relevance
“…A reduction in the seasonal amplitude of AA with increased CO 2 forcing was also found in a study using a single model [41]. That, and another study [48], also found that the peak in AA shifted from late autumn to early winter over the 21st century, with our results here suggesting that is caused by a decrease in autumn AA, while winter AA remains approximately constant.…”
Section: Model Uncertaintysupporting
confidence: 90%
“…A reduction in the seasonal amplitude of AA with increased CO 2 forcing was also found in a study using a single model [41]. That, and another study [48], also found that the peak in AA shifted from late autumn to early winter over the 21st century, with our results here suggesting that is caused by a decrease in autumn AA, while winter AA remains approximately constant.…”
Section: Model Uncertaintysupporting
confidence: 90%
“…There is also a strong seasonality to Arctic amplification with the largest amplification occurring in the winter months due to the combination of a more stably-stratified atmosphere [15], the effective heat capacity of sea ice [21], and ocean-mediated seasonal transfer of energy between ocean, sea ice, and atmosphere [22]. This seasonality is expected to change under increased CO 2 forcing with the peak moving later in the season [23,24]. While there is not a consensus on the relative importance of the processes behind Arctic amplification, many approaches including the evaluation of climate models using radiative kernels have shown that the sea-ice albedo feedback and atmospheric stability are two of the most important processes [25].…”
Section: Introductionmentioning
confidence: 99%
“…This finding was further supported through a decomposition of the Arctic LRF into "upper" and "lower" troposphere contributions, showing that this feedback arises primarily as an atmospheric response to the local sea-ice loss, although it is reduced in subpolar latitudes by an enhanced poleward atmospheric energy transport 10 . The uncertainty in Arctic climate projections is dominated by model differences (rather than internal climate variability or even scenario uncertainty) and shifts gradually from autumn to winter over the 21 st century, in line with a dominant influence of the sea ice retreat that also shows a similar seasonal shift 11 .…”
Section: Confidential Manuscriptmentioning
confidence: 92%